Strategi Pembinaan Generasi Muda Hindu Dalam Meningkatkan Sradha dan Bhakti dikalangan Seka Teruna-Teruni - Ni Wayan Murniti; Komang Dewi Susanti; Ni Luh Purnamasuari Prapnuwanti (Jayapangus Press, 2022)
This study aims to improve the Sradha and devotion of the younger generation of Hindus as the next generation in order to become a young generation of virtuous character, and faith. As well as to describe the strategy of fostering the younger generation of Hindus with educational studies. Given that the younger generation of Hindus is currently experiencing a moral decline as a result of the influence of the waning of religious attitudes. This research is expected to be used as a contribution of thought in formulating policies and making decisions on similar problems faced in the future, besides that this research is also expected to be able to add scientific readings, as well as a reference for students who will conduct further research on the same problem. . This type of research is qualitative research. This research was conducted in Buleleng District by involving sekaa teruna- eruni as respondents. Data obtained through observation data, interviews, document recording, literature study. The results showed (1) The pattern and strategy of fostering the younger generation of Hindus in improving Sradha and devotional service among the sekaa teruna-teruni of the Buleleng Traditional Village (2) The obstacles faced in increasing Sradha and devotional service among the sekaa teruna-teruni in Desa Pakraman Buleleng were influenced by two factors, namely: (1) internal factors, including; (a) Individual sekaa teruna-teruni in the Buleleng Traditional Village, (b) individual sekaa administrator for teruna-teruni (3) Efforts are being made to overcome obstacles in fostering the younger generation of Hindus in improving Sradha and devotional service among sekaa teruna-teruni in Buleleng Traditional Village.